Association of the DNA repair genes polymorphism with the frequency of chromosomal mutations and health status of the population of the Almaty region (International Journal of Biology and Chemistry, 2021)
The study utilized molecular-genetic, cytogenetic, and statistical analyzes methods. A cytogenetic and molecular genetic analysis of the inhabitants of the villages of Amangeldy, Belbulak, in whose territory warehouses of unused pesticides are located, was carried out. Residents of the Basshi village, on the territory of which there are no products of disposal of pesticides, were taken as control. Cytogenetic analysis showed a high level of chromosomal aberrations for the inhabitants of the Belbulak village, an increased level for the inhabitants of the Amangeldy village and a low level in the Basshi cohort. Molecular genetic analysis did not reveal a significant correlation between the polymorphisms of the XRCC1 Arg194Trp, XRCC3 Thr241Met and XPD Lys751Gln genes and the frequency of chromosomal aberrations. However, study determined the associative relationship of the polymorphism of the DNA repair gene XRCC1 Arg399Gln with the development of cardiovascular diseases in a population living near foci of pesticidal contamination.